Civil Soceity Asks For Mechanisms For Broader And Regular Monitoring Of Access To Essential Medicines In The Next Uganda Pharmaceutical Plan - HEPS-Uganda (HEPS-Uganda, 2017)
Uganda’s Constitution and National Drug Policy recognise access to medicines – a fundamental element of the right to health1 – as a goal of State health programmes and interventions. The Constitution requires the State to take all practical measures to ensure the provision of basic medical services, of which medicines are an essential part, to the population.2 And, through the National Drug Policy, the State accordingly aims to ensure the availability and accessibility of adequate quantities of affordable, efficacious, safe, and high quality essential medicines and health supplies (EMHS)3 to all people at all times. In an effort to achieve access, Government and development partners, have increased funding for EMHS and implemented reforms in the logistics and supply chain system. In 2008/09, total Government and donor EMHS expenditure on (including for this period off-budget projects) was estimated at US$139 million (Ushs 347 billion) or about $ 4.5 per capita.4 In this regard, the U.S. Government was the largest single source of EMHS funding (35.4% of total expenditure) followed closely by Government of Uganda (33.4%) and then by CHAI (10.4%), Global Alliance for Vaccines and Immunization 9.5%, and The Global Fund to Fight AIDS, Tuberculosis and Malaria 4% and other development partners 7.3%. One of the most important reforms has been the creation of a separate budget vote for EMHS (Vote 116) effective July 2009. In 2011/12, EMHS funding through National Medical Stores (NMS) – handling only about one half of medicines consumed in the public and private-not-for-profit sectors – only reached Ushs204 billion.5 Another major reform has been a move away from a “pull system” to a “push system” of EMHS for lower-level health facilities, which a pre-determined kit or basket of EMHS.